DEVELOPMENT OF ASSESSMENT INSTRUMENTS FOR TEACHERS USED IN ASSESSING HIGH SCHOOL STUDENTS' EXPOSITION WRITING: A SYSTEMIC FUNCTIONAL APPROACH - Harjuli Surya Putra (Journal of Language, Literature and Teaching, 2021)
This research aims at developing a writing assessment rubric for a exposition text. This rubric is made in accordance with the assessment standard of the current Senior High School curriculum, Kurikulum Tingkat Satuan Pendidikan (KTSP) to be used by the teachers. Based on observations made of two high school English teachers at SMA Negeri 19 Medan , it was found that the assessment of students' writing in class XI was done by simply giving points or grades without any clear criteria. Such assessments tend to be subjective, inaccurate, and are not helpful for students. One way to overcome this is to use an assessment rubric. The development of this rubric was done through 7 stages of development, namely research and information collection, planning, developing premilinary forms of the product, premilinary field testing, main product revision, main field testing, and operational product revision. The development of this rubric is based on 16 students' writing. Analysis of data in this study was conducted by analyzing and assessing students' writing in first and second drafts as well as the results of the first and second questionnaires and interviews. The results show a rubric that can be used by the teacher to score students’ writing. Key words:writing, genre, rubric, assessment